ARABIC- THE EFFECT OF PROPHETIC MEDICINE ON HEALTH AWARENESS: CORONA EPIDEMIC AS A MODEL - Masood Ahmad; Bashir Bahar Gadam (دی اسکالر)
The modern world today, the Covid-19 Corona epidemic is sweeping the entire world, as people on earth have become prisoners of diseases that kill them without discrimination, gender or color, as it affects the ruler, princes and kings - the rich and the poor - and it has greatly damaged the social and health environment until it is no longer. People meet as they once were. Rather, people are fleeing from each other, especially sick people or those accused of this deadly epidemic as fleeing from the hungry lion or hating it as they hate meeting the enemy.The Corona epidemic blocked the wide horizon, closed commercial activities, and paralyzed life, as it became difficult for people to move from place to place completely freely. Rather, the military is from that, as governments around the world have been keen to emphasize the movement of citizens, and to close markets, shops, restaurants, and hotels, and have gone further than that by preventing public gatherings in addition to the gathering of more than five individuals in one place. In the first cycle of the spread of Corona disease, governments sought to close airports and prevent travel between cities in the same country, in addition to travel between different countries. This increased isolation between countries. From what seriously affected the economic activities. Some countries did not pay attention to this ban and did not take it seriously at first, which increased the spread and transmission of infection from sick people to healthy people.